The Effectiveness of Problem-Based Learning in Statistics on Mathematical Problem-Solving Ability Across Polya’s Stages - Siti Rohiimah; Kismiantini (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study examined the effectiveness of Problem-Based Learning (PBL) in improving students’ mathematical problem-solving ability in Statistics across Polya’s problem-solving stages. A quantitative pre-experimental approach with a One-Group Pretest–Posttest design was employed involving 31 eighth-grade students selected through purposive sampling. Data were collected using a mathematical problem-solving test and analyzed using descriptive statistics, normalized gain (N-Gain), and Paired Sample t-test. The results revealed a significant improvement in students’ mathematical problem-solving ability after the implementation of PBL (p < 0.05). The average N-Gain score was 0.59, indicating a moderate level of improvement, while classical mastery increased from 9.68% to 83.87%. Across Polya’s stages, the greatest improvement was observed in planning and carrying out solution strategies, whereas the reviewing stage remained the least developed. These findings indicate that PBL is effective in enhancing students’ mathematical problem-solving ability and suggest the need for explicit metacognitive support to strengthen reflective thinking during problem-solving activities.